Praktikalitas E-Learning Berbasis Web di SMK Dhuafa Padang Tahun Ajaran 2022-2023 - Riza Azizi; Astri Indah Juwita; Rahmatul Husna Arsyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is motivated by the problem of limited learning media at SMK Dhuafa Padang. This happens because there is no media-based learning that is attractive and effective. Therefore, the author seeks to design and create learning media for e-learning based on the Web at SMK Dhuafa Padang. This study uses research and development (R&D) methods. The research model used is the Borg & Gall development model, with the design and development steps as follows: Research and Information Gathering Stage (literature study, field study, user analysis); Planning (strengths, weaknesses, opportunities, threats); Product Development (waterfal: analysis, design, code); Product Testing and Revision (instrument validation, media validation); Final Product Revision (field trials, practicality, effectiveness); Dissemination. The research subjects were 75 students and 10 teachers. The results of the validity test by the experts as a whole are an assessment of the validity of E-learning based Web in Padang Dhuafa Vocational School of 88.53%, so that the validity level can be interpreted as very valid for use. The results of the practicality test assessment as a whole practicality assessment of E-learning based Web in Padang Dhuafa Vocational School were 94.49%, so that the level of practicality can be interpreted as being very practical to use. The results of the overall effectiveness test assessment of the effectiveness assessment E-learning  based Web in Dhuafa Padang Vocational School were 94.85%, so that the level of effectiveness can be interpreted as being used very effectively.